The Effect of Profitability and Leverage on Firm Value with Managerial Ownership as a Moderating Variable in Telecommunication Companies - Indra Palguna; I Gusti Ayu Made Asri Dwija Putri (PT. INOVASI TEKNOLOGI KOMPUTER, 2026)
Evidence that investors assess company performance based on ownership composition impacting management choices in addition to profitability and capital structure serves as the driving force for this study. With management ownership acting as a moderator, it seeks to investigate how profitability and leverage affect firm value in telecommunications businesses that are listed on the Indonesia Stock Exchange between 2018 and 2023. Businesses having comprehensive financial records were chosen using a quantitative method and purposive sampling. Return on equity (ROE), debt to equity ratio (DER), firm value (PBV), and managerial ownership (% of shares held by management) were used to gauge profitability. The findings show that while leverage has no discernible impact on business valuation, profitability has a positive and considerable impact, indicating that investors are not particularly concerned about debt structure. The relationship between business value and profitability is not moderated by managerial ownership. The relationship between leverage and business value is not moderated by managerial ownership. The study adds to the body of knowledge on corporate governance